Distributional mapping and impacts of invasive alien fish in Indonesia : an alert to inland waters sustainability - Rahmi, Dina; Gema, Wahyudewantoro; Sekar, Larashati; Siti Aisyah,; Lukman,; Sulastri,; Imroatushshoolikhah,; Sopian, Sauri (Penerbit Universiti Kebangsaan Malaysia, 2022)
Inland water ecosystems in Indonesia face an increasing threat of alien and invasive alien fish species. Their existence have been found in Indonesian waters since before 1900, and their introduction is rapid and ongoing. In this review, we mapped the distribution of alien and invasive alien fish in different inland waters ecosystem types and islands in Indonesia, based on available literature indexed by Google Scholar. Impacts of invasive alien fish and how to control them are also discussed. This data mining exercise resulted in the successful mapping of alien and invasive alien fish in 72 lakes and 57 river systems, covering 28 provinces. A total of 50 species have spread with different compositions in each type of ecosystem and island. Oreochromis niloticus is the most commonly encountered alien species. Moreover, invasive cichlid fish are most frequently found in lakes, while Pterygoplichthys spp. are more frequently found in rivers although they can also inhabit many lakes. Java Island is a hotspot of alien and invasive alien fish distribution, with 39 species reported. Invasive alien fish harm native and endemic fish in Indonesia through competition for food, space and direct predation. The gradual reduction of established populations of invasive alien species is necessary to protect Indonesia’s freshwater ecosystems.